Dirasat in Economics and Business MOTIVATION AND INCENTIVES A COMPARATIVE STUDY - Amer, Dr. Abdulgader A. (Dirasat in Economics and Business, 1979)
The objective of this article is to examine how the free market system differs from the Third Universal Theory in deal ing with the problem of motivation and incentives. Some approaches to the motivation of producers in the free market system, such as profit-sharing, management throngh use of participation, management by objectives, and job enrichment are discussed.